2014
DOI: 10.4271/2014-01-0594
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Aerodynamics of a Realistic Car Model by Means of RANS and Hybrid RANS/LES Approaches

Abstract: The aerodynamic properties of a BMW car model, representing a 40%-scaled model of a relevant car configuration, are studied computationally by means of the Unsteady RANS (Reynolds-Averaged Navier-Stokes) and Hybrid RANS/LES (Large-Eddy Simulation) approaches. The reference database (geometry, operating parameters and surface pressure distribution) are adopted from an experimental investigation carried out in the wind tunnel of the BMW Group in Munich (Schrefl, 2008). The present computational study focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A recent work by Peters et al [19], which presented higher order structured finite difference solutions using overset grids and NASA's overset grid solver Overflow, also observed similar pressure distribution differences when using the SST k − ω model. Moreover, several widely-used RANS and hybrid LES/RANS models were also applied to the DrivAer model [1,2,20,21]. It was found that RANS models were unable to predict the force coefficients correctly, especially the lift coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…A recent work by Peters et al [19], which presented higher order structured finite difference solutions using overset grids and NASA's overset grid solver Overflow, also observed similar pressure distribution differences when using the SST k − ω model. Moreover, several widely-used RANS and hybrid LES/RANS models were also applied to the DrivAer model [1,2,20,21]. It was found that RANS models were unable to predict the force coefficients correctly, especially the lift coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…They range from relatively simple square section infinite cylinders [26] to complete cars [27]. For a review of previous simulations, we refer to [28].…”
Section: Experiences Of Pans Of Bluff Body Flowsmentioning
confidence: 99%
“…Consequently, a common practice for turbulent simulation of industrial interest is to adopt the RANS turbulence modeling approach. However, RANS models are single-point closures, relying on the assumption of self-similarity of the turbulence spectrum [17]. This assumption suggests that the complete turbulence spectrum can be defined by a single characteristic turbulent length scale.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it offers enhanced outcomes compared to the RANS method, while demanding significantly less computational resources than LES calculations. The successful implementation of the PANS technique has been demonstrated across a wide range of applications (see [17,[20][21][22]). Various PANS variants have been developed to date; for this study, a PANS model based on the k − ζ − f model proposed by Basara et al [23] is coupled with the FGM tabulated chemistry combustion model.…”
Section: Introductionmentioning
confidence: 99%